Relationship between nurses spent time for care and patients satisfaction in internal ward in Gorgan 5th Azar Hospital - Gh Rouhi; SA Hosseini; H Asayesh; N Behnampoor; H Rahmani (Tehran University of Medical Sciences, 2009)
Background and Aim: Today provision of an adequate and appropriate health services depend on many factors. Human resources are one of the most important factors. Nursing managers with more exact understanding of nursing activity could prevent of human resource wastage. In other way goal achievement in an efficient remedial system depends upon favorite delivery services and one of the appropriate ways for quality of care evaluation is patient satisfaction measurement about care delivery. This study was conducted and implemented to measure the nursing care time and its relationship with patient satisfaction. Materials and Methods: This descriptive and analytical study was done in internal ward in Gorgan 5th Azar educative and therapeutic center for one month. nursing activity checklist was used for measuring the time that spend for Nursing staff activity and patient satisfaction scale. Data were analyzed with SPSS for Windows package. Results: In this research findings showed, 46.46% of nursing activity time was spent for direct care, 15.8% of total time was used for documentation activities and 22.5% of time spent for nurses' individual activity, whereas only 7.43 percent of total time was spend for patient assessments. 60.3% of patients were satisfied about care delivery and 24.8% of them had moderate satisfaction. A significant correlation was seen between patient satisfaction and nursing direct care (r =0.272, P= 0.001).By increasing The spent time for direct care, patients' satisfaction was also increased. Discussion and Conclusion: Nursing managers' awareness from scientific methods of management, rules modification, use of new equipment and technology and also delegating of some nursing activity to nursing assistants could promote quality of care with increasing of nursing direct care.